Mitigation of Environmental Exposure, Pollutants, and Endocrine Disruptors to Reproductive Health: A Literature Review - Nur Afidarti; Open Darnius; Diah Lestari Nasution; Evi Indriani Br Karo (Caring: Indonesian Journal of Nursing Science, 2025)
Women's reproductive health faces escalating threats from environmental pollutants, including airborne particulate matter (PM2.5 and PM10), endocrine-disrupting chemicals (EDCs), heavy metals, and microplastics. These pervasive agents, found in air, food, water, and consumer products, are associated with hormonal imbalances, menstrual irregularities, infertility, adverse pregnancy outcomes, and long-term reproductive dysfunction. This literature review synthesizes current evidence on environmental exposures, specifically focusing on pollutants and EDCs impacting reproductive health. Adhering to the PRISMA framework, articles published between 2020 and 2024 were systematically identified from databases such as PubMed, ScienceDirect, and Google Scholar. Manual selection based on predefined inclusion criteria ensured the relevance and recency of included studies. Findings consistently demonstrate that air pollutants (PM2.5 and PM10) correlate with reduced ovarian reserve and altered estradiol levels. EDCs, such as Bisphenol A (BPA) and phthalates, are linked to early puberty, endometriosis, and infertility. Heavy metals influence age at menarche and menopause, as well as critical pregnancy outcomes like birth weight. Furthermore, microplastics and nanoplastics have been shown to impair placental function and elevate oxidative stress. These cumulative findings underscore the urgent need for comprehensive risk mitigation strategies, encompassing environmental education, behavioral modifications, clinical screening, and policy reform. Nurses are uniquely positioned to play a critical role in promoting reproductive health through education, early detection of environmental risks, and advocacy for safer community environments.